Integralism and schools in Blumenau: obliterated interlocutions in the historical narratives (PerCursos, 2024)
For a long time, Blumenau's schools were not investigated and were not always recognized for articulating relationship that provided political arrangements capable of influencing public life.  Identified by the integralism, organized in the city in 1934, in which was present in schools through individuals vinculated to the school functions and the militia group, it was possible to advance in understanding about the reasons that contributed to the vast valorization of Brazilian Integralist Action (AIB) in Blumenau. Despite being a movement interested in the defense of national elements, encouraging the participation of immigrants and descendants of germans as supporters of integralism, including those who only spoke the german language, seems not to have been considered incoherent. The integralists João Ehlert and Aristides Largura, teacher and school inspector respectively, demonstrated to understand the importance of the relations that could be established through schools to ensure both the expansion of integralism among the population of german origin and the maintenance of their ethnic reference, often, not interested in the national integration.
Keywords: schools; integralism; politic; nationalism